Leveraging learning forces in asymmetric alliances: small firms’ perceived power imbalance in driving exploration and exploitation - Hao, Bin; Feng, Yanan (Elservier, 2018)
Prior studies on power and interfirm learning in alliances have devoted limited attention to multiplicate influences of diverse power sources on exploration and exploitation and whether such influences on these two strategies are similar or different. This study investigates the joint effects of two types of perceived power—capability-driven power and position-driven power—on exploration versus exploitation in asymmetric alliances. Using a sample of 205 high-technology firms in China, the analyses suggest that each of the two types of perceived power separately has no direct effects on either exploration or exploitation. However, they complement (multiplicative effects) each other in promoting exploitation and exploration. Interestingly, the balanced effect of perceived position-driven power and perceived capability-driven power is positively related to exploration, while no such an impact is found in terms of exploitation. This study provides alternative insights about inter-organizational learning in asymmetric alliances and points out a direction for future research.